PENGARUH MACAM EKSTRAK BAHAN ORGANIK DAN ZPT TERHADAP PERTUMBUHAN PLANLET ANGGREK HASIL PERSILANGAN PADA MEDIA KULTUR - Sri Hartati (Caraka Tani: Journal of Sustainable Agriculture, 2010)
This research aimed to study the effect of kinds of culture media composition added with organic matter (soya bean extract, corn extract and fish emulsion) and PGR concentration to the growth of each cross breed orchid explants. Research was conducted in Plant Physiology and Biotechnology Laboratory, Agriculture Faculty, Sebelas Maret University of Surakarta from March 2009 until the end. This research was done in Randomized Completely Design with two factors of treatment and four replications. The first factor was media and organic matter, consist of 3 levels: soya bean extract, corn extract and fish emulsion. The second factor was atonik concentration, consist of 3 levels: 0 cc/l, 0.5 cc/l and 1 cc/l. The research concluded that for the explants of crossing (Phalaeonopsis pinlong cinderela ♀ >< Phalaeonopsis joanekileup June” ♂) two treatment of corn extract affected significantly to the root emergence time (21.33 ) and member of root (1,92 day after planting) The treatment of fish emulsion affected significantly to the root length (2,82 cm), number of root (1,92) and produced the longest leaf. The treatment of Atonik increased the number of leaf and root.